Experimental Autoimmune Encephalomyelitis Is Successfully Controlled by Epicutaneous Administration of MOG Plus Vitamin D Analog - Zorzella-Pezavento, Sofia Fernanda Gonçalves; Mimura, Luiza Ayumi Nishiyama; Fraga-Silva, Thais Fernanda Campos; Ishikawa, Larissa Lumi Watanabe; França, Thais Graziela Donegá; Sartori, Alexandrina (Frontiers in Immunology, 2017)
Multiple sclerosis (MS) is an inflammatory and demyelinating disorder of the central nervous system (CNS). Experimental autoimmune encephalomyelitis (EAE) has been widely employed to evaluate new strategies to control MS, including procedures to induce immunological tolerance. Considering that skin exposure to protein antigens can induce tolerance and that vitamin D analogues conserve immunomodulatory potential and are less toxic, we investigated the efficacy of epicutaneous application of a myelin oligodendrocyte glycoprotein peptide (MOG35-55) associated with paricalcitol (PARI) on EAE development. Three and eleven days after EAE induction, C57BL/6 mice were treated with an occlusive patch containing MOG plus PARI. Clinical parameters were daily assessed, whereas immunological and histological evaluations were performed during the acute EAE phase. MOG and MOG+PARI significantly controlled disease development reducing weight loss and clinical score. Moreover, MOG and MOG+PARI reduced the inflammatory process and preserved the myelin sheath in the CNS. High percentages of Foxp3+ regulatory T cells (Treg) and lower MHCII fluorescence intensity in myeloid dendritic cells in draining lymph nodes were concomitantly observed. MOG+PARI association was, however, more efficient being able to reduce disease incidence and clinical scores more significantly than MOG or PARI alone. This experimental group also displayed a higher ratio between mRNA expression for Foxp3+ and RORc and a higher percentage of Foxp3+ cells in the CNS. Modulation of activation markers observed in microglial cells eluted from EAE treated mice were confirmed by in vitro studies with the BV-2 microglial cell line. The results show that MOG+PARI association applied by an epicutaneous route controlled EAE development. Protective involved mechanisms include mainly a higher proportion of Treg cells and also a direct immunomodulatory effect of PARI on microglial cells.